Surgical approach to multifocal hepatocellular carcinoma with portal vein thrombosis and arterioportal shunt leading to portal hypertension and bleeding: a case report - Ratti Francesca (World Journal of Surgical Oncology, 2012)
Abstract It is reported the case of a 69 years man who presented to the Emergency Room because of pain and abdominal distension from ascites. After admission and paracentesis placement, he developed a digestive hemorrhage due to oesophageal varices from portal ipertension secondary to the formation of a portal shunt concomitant with a multifocal HepatoCellular Carcinoma (HCC) with portal vein thrombosis (PVT). The patient underwent endoscopic varices ligation, twice transarterial embolization (TAE) of arterial branches feeding the shunt and subsequent left hepatectomy. During the postoperative course he developed mild and transient signs of liver failure and was discharged in postoperative day 16. He is alive and disease free 8 months after surgery.